RELATIONSHIP BETWEEN LEXICAL TONE CONTRASTS AND VOWEL QUALITY - Kofi Adu Manyah (European Scientific Journal, ESJ, 2014)
The language under study is Twi, a register tone language of the Kwa group, spoken in Ghana. It has a two tone system (high/low) and the downstep phenomena. The aim of this paper is two-fold. First, some phonological aspects of Twi tones are described. Second, acoustic measurements are carried out to investigate for differences between vowel quality in the two groups. In this analysis, two adult male speakers and one female adult speaker produced a series of isolated words belonging to the two phonological classes. The evidence from our acoustic data, confirming results obtained in a preliminary study, is for high tones to have higher fundamental frequency values than low tones. Acoustic results also confirm that high and low tones show sparse qualitative (F1, F2, F3 and F4) as well as sparse syllabic durational differences. The tendency is also for low tones to have lower F1, higher F2 than the high counterparts.